Digitalizarea serviciilor sociale în Moldova: rezultate, provocări, tendințe [Articol] - Lungu, Tatiana; Marin, Danu; Cebotari, Svetlana (CEP USM, 2022)
La nivel global, implementarea inițiativelor de transformare digitală a devenit una dintre principalele preocupări. Guvernul Republicii Moldova, împreună cu agențiile sale responsabile cu dezvoltarea și furnizarea de servicii sociale, și-au îndreptat tot mai mult atenția către platforma digitală pentru a inova și a furniza servicii sociale cât mai multor persoane la nivel național.

Globally, the implementation of digital transformation initiatives has become one of the main concerns. The Government of the Republic of Moldova, together with its agencies, responsible for the development and provision of social services, have increasingly turned their attention to the digital platform to innovate and deliver social services to as many people as possible at the national level.
DIGITALIZATION OF SOCIAL SERVICES IN MOLDOVA: RESULTS, CHALLENGES, TRENDS
Keywords: digitalizare; guvernarea digitală; e-guvernare; servicii publice; COVID-19; refugiați